Quantitative X-ray phase-contrast computed tomography at 82 keV - Willner, Marian; Bech, Martin; Herzen, Julia; Zanette, Irene; Hahn, Dieter; Kenntner, Johannes; Mohr, Juergen; Rack, Alexander; Weitkamp, Timm; Pfeiffer, Franz (Optics Express, 2013)
Potential applications of grating-based X-ray phase-contrast imaging are investigated in various fields due to its compatibility with laboratory X-ray sources. So far the method was mainly restricted to X-ray energies below 40 keV, which is too low to examine dense or thick objects, but a routine operation at higher energies is on the brink of realisation. In this study, imaging results obtained at 82 keV are presented. These comprise a test object consisting of well-defined materials for a quantitative analysis and a tooth to translate the findings to a biomedical sample. Measured linear attenuation coefficients m and electron densities re are in good agreement with theoretical values. Improved contrast-to-noise ratios were found in phase contrast compared to attenuation contrast. The combination of both contrast modalities further enables to simultaneously assess information on density and composition of materials with effective atomic numbers Z > 8. In our biomedical example, we demonstrate the possibility to detect differences in mass density and calcium concentration within teeth. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08